Título Padrão - Maciel, Francisco Ramon de Matos (Em Perspectiva, 2020)
The migration of rural poor people from the interior of Ceará, Paraíba and Rio Grande do Norte, to the towns and coastal cities, revealed forms of agency and popular politics in episodes of revolts and insurrections during the droughts of 1877 and 1879. These upheavals, in many cases, answered the question of the distribution of foodstuffs by the public help commissions. Which were created by the provincial presidents to assist the migrant population clustered in and around urban space. The looting of warehouses, both privately and publicly owned, were some of the collective actions that the backcountry found in order to create dialogue and to pressure local authorities to get staple foods. In the end, the migrants would typically distribute the food amongst themselves after obtaining it. This research examines "hunger riots"; became a social phenomenon that broke the provincial borders of the northern empire during the droughts of 1877 and 1889. The partial results of the paper indicate that the forms of agency of the migrants in the great droughts of the nineteenth century became a social phenomenon with strong political elements of the subordinate classes.